(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Pelvic syncography is the imaging modality of choice for evaluating the animal pelvis. Does not use ionizing radiation (which can cause cancer and birth defects in the fetus). How the images are taken, the direction of the image, and how the sound waves move are checked. We examine the view of the anatomy of the divided uterus and ovary.